Simulation of percolation threshold and electrical conductivity in composites filled with conductive particles: Effect of polydisperse particle size distribution. Issue 1 (12th August 2014) - Arenhart, R.G.; Barra, G.M.O.; Fernandes, C.P.
Abstract : A Monte Carlo simulation method was developed in the open source programing language Python to predict the conductive filler concentration at the percolation threshold and the electrical conductivity for different filler concentrations in electrically conductive composites (ECCs) with fiber‐like conductive fillers. The computer method was programmed to consider the aspect ratio distribution of the fibers or a single average aspect ratio for the determination of the percolation threshold. The results for the two cases were compared to values reported in the literature for liquid crystal polymers (LCP) with synthetic graphite (SG) and to results obtained experimentally for polyvinylidene fluoride (PVDF) with polypyrrole (PPy)‐coated amorphous silica fibers (ASF). Additionally, a contact resistance based on the tunneling effects principle was used to predict the electrical conductivity, and the results of the simulations were compared to the experimental data for the same ECCS. It was found that the percolation thresholds predicted through the simulations considering the aspect ratio distribution were within the concentration limits associated with the transition from electrical insulation to conductivity, while the electrical conductivity predictions had similar behavior to the experimental data, although the values were of different magnitudes. POLYM. COMPOS., 61–69, 2016. © 2014 Society of Plastics Engineers